Adaptive Stochastic GERT Modeling of UAV Video Transmission for Urban Monitoring Systems - Semenov, Serhii; Krupska-Klimczak, Magdalena; Frontczak, Michał; Yu, Jian; He, Jiang; Chernykh, Olena (MDPI, 2025)
The growing use of unmanned aerial vehicles (UAVs) for real-time video surveillance in smart city and smart region infrastructures requires reliable and delay-aware data transmission models. In urban environments, UAV communication links are subject to stochastic variability, leading to jitter, packet loss, and unstable video delivery. This paper presents a novel approach based on the Graphical Evaluation and Review Technique (GERT) for modeling the transmission of video frames from UAVs over uncertain network paths with probabilistic feedback loops and lognormally distributed delays. The proposed model enables both analytical and numerical evaluation of key Quality-of-Service (QoS) metrics, including mean transmission time and jitter, under varying levels of channel variability. Additionally, the structure of the GERT-based framework allows integration with artificial intelligence mechanisms, particularly for adaptive routing and delay prediction in urban conditions. Spectral analysis of the system’s characteristic function is also performed to identify instability zones and guide buffer design. The results demonstrate that the approach supports flexible, parameterized modeling of UAV video transmission and can be extended to intelligent, learning-based control strategies in complex smart city environments. This makes it suitable for a wide range of applications, including traffic monitoring, infrastructure inspection, and emergency response. Beyond QoS optimization, the framework explicitly accommodates security and privacy preserving operations (e.g., encryption, authentication, on-board redaction), enabling secure UAV video transmission in urban networks.
Keywords: UAV video transmission; GERT modeling; smart city; stochastic delay; jitter analysis; Quality of Service (QoS); spectral analysis; probabilistic networks; adaptive communication; artificial intelligence integration; security-aware routing; privacy-preserving video; UAV; urban networks